(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Water supplies are becoming scarce these days, and a large volume of wastewater is being pumped into the atmosphere by various industries. To reduce the amount of contaminants in wastewater, various approaches are used. Therefore, the productive treatment of wastewater is required in emergent for resolving this problem. Expanding and implementing advanced wastewater treatment systems with greater efficiency and lower capital requirements are critical. Recent advanced processes in nano-material sciences have enchanted scientist’s attention with a variety of treatments. This script does, however, have a small amount of collective expertise. Nanomaterials have been the theme of strong research and development in current years all over the world. Because of the unique properties that ended from the nanoscale size, such as enhanced catalysis and adsorption property, also high reactivity. This background examines the possible applications of nanotechnology in wastewater treatment. Nanomaterials have been shown in a few studies to be effective at removing different toxins from water, and successfully implemented in water and wastewater treatment. The most broadly researched nanomaterials for wastewater treatment, zero-valent metal nanoparticles (Ag, Fe, and Zn), metal-oxide nanoparticles (TiO2, ZnO, and iron oxides), carbon nanotubes (CNTs), and nanocomposites, are conferred and tinted detail in this paper.